2013
DOI: 10.1111/tpj.12092
|View full text |Cite
|
Sign up to set email alerts
|

Potassium transport in developing fleshy fruits: the grapevine inward K+ channel VvK1.2 is activated by CIPKCBL complexes and induced in ripening berry flesh cells

Abstract: SUMMARYThe grape berry provides a model for investigating the physiology of non-climacteric fruits. Increased K + accumulation in the berry has a strong negative impact on fruit acidity (and quality). In maturing berries, we identified a K + channel from the Shaker family, VvK1.2, and two CBL-interacting protein kinase (CIPK)/calcineurin B-like calcium sensor (CBL) pairs, VvCIPK04-VvCBL01 and VvCIPK03-VvCBL02, that may control the activity of this channel. VvCBL01 and VvCIPK04 are homologues of Arabidopsis AtC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 40 publications
4
79
0
Order By: Relevance
“…Several AKT1 orthologs have been identified in other plant species, such as Os-AKT1 in rice (Oryza sativa; Fuchs et al, 2005), Zm-ZMK1 in maize (Zea mays; Philippar et al, 1999), Ta-AKT1 in wheat (Triticum aestivum; Buschmann et al, 2000), Hv-AKT1 in barley (Hordeum vulgare; Boscari et al, 2009), Sl-LKT1 in tomato (Solanum lycopersicum; Hartje et al, 2000), and St-SKT1 in potato (Solanum tuberosum; Zimmermann et al, 1998). Similar regulatory mechanisms, with CBL-CIPK complex-modulating K + channels, were also reported in barley (Boscari et al, 2009) and grape (Vitis vinifera) plants (Cuéllar et al, 2010(Cuéllar et al, , 2013.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Several AKT1 orthologs have been identified in other plant species, such as Os-AKT1 in rice (Oryza sativa; Fuchs et al, 2005), Zm-ZMK1 in maize (Zea mays; Philippar et al, 1999), Ta-AKT1 in wheat (Triticum aestivum; Buschmann et al, 2000), Hv-AKT1 in barley (Hordeum vulgare; Boscari et al, 2009), Sl-LKT1 in tomato (Solanum lycopersicum; Hartje et al, 2000), and St-SKT1 in potato (Solanum tuberosum; Zimmermann et al, 1998). Similar regulatory mechanisms, with CBL-CIPK complex-modulating K + channels, were also reported in barley (Boscari et al, 2009) and grape (Vitis vinifera) plants (Cuéllar et al, 2010(Cuéllar et al, , 2013.…”
Section: Introductionsupporting
confidence: 56%
“…In X. laevis oocytes, Vv-K1.2 alone could not form functional channel. However, after coexpression with Vv-CBL01-Vv-CIPK04 or Vv-CBL02-Vv-CIPK03, Vv-K1.2 was capable of mediating inward K + currents (Cuéllar et al, 2013). It seems that the regulation of AKT1-like channels via a CBL-CIPK complex might be a universal mechanism in different plant species.…”
Section: The Regulatory Mechanism Of Akt1-like Channels In Plantsmentioning
confidence: 99%
“…These genes are known ABA targets that are also important for berry ripening . Indeed, together with sugar accumulation, K + influx might help the turgor-driven berry expansion , and the K + channel VvK1.1 may play a major role in K + loading into berry tissues, especially upon drought stress (Cuéllar et al, 2010(Cuéllar et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…When VvCIPK03-VvCBL02 were co-expressed with VvK1.2, much smaller K + currents were generated. VvCBL01 and VvCIPK04 were also found to control the activity of AKT1 in Arabidopsis roots (Cuéllar et al 2013 ). Recently, it was shown that co-expression of either AtCBL1 or AtCBL9 with AtCIPK26 strongly enhances ROS production by phosphorylating NADPH oxidase RBOHF (Sagi and Fluhr 2006 ;Kimura et al 2013 ;Drerup et al 2013 ).…”
Section: Oscbl8mentioning
confidence: 97%